Israel's scriptures in early Christian writings the use of the Old Testament in the New - Henze, Matthias 1965-; Lincicum, David 1979- (William B. Eerdmans Publishing Company, 2023)
"An essay collection on the use of the Old Testament by New Testament authors"--
Keywords: Bibel -- Altes Testament; Bibel -- Neues Testament; Rezeption; Frühchristentum; Bible / New Testament / Relation to the Old Testament; Bible / Old Testament; Bible / Old Testament / Criticism, interpretation, etc; Bible / New Testament / Criticism, interpretation, etc; Aufsatzsammlung